Bibliometric Analysis of Procurement Ethics and Supplier Management - Judijanto, Loso; Hamzali, Said; Utami , Eva Yuniarti (West Science Interdisciplinary Studies, 2025)
This study conducts a bibliometric analysis to map the intellectual structure, thematic trends, and collaborative patterns within the field of procurement ethics and supplier management. Using data from the Scopus database and visualized through VOSviewer, the analysis covers co-authorship networks, keyword co-occurrence, citation structures, and country-level collaboration. Results show that "supplier management" remains the dominant theme, closely linked to operational concerns such as supplier selection, quality control, and risk management. More recent trends reveal a growing integration of sustainability, artificial intelligence, and information technology into procurement practices. Co-authorship and country collaboration networks highlight influential researchers and global research hubs, particularly in Germany and the United States. Despite progress, ethical constructs are often framed through strategic or technological lenses rather than normative perspectives. The study provides a roadmap for future research, emphasizing the need for broader ethical engagement and greater inclusivity of emerging economies in global procurement discourse.